The Effectiveness of Using Coloured Blocks in Teaching the Concept of Balancing Chemical Equation in Chemistry - Razreena Ridzuan; Zanaton H. Iksan (Journal of Educational Sciences, 2017)
The aim of this study is to study the effectiveness of using coloured blocks in teaching the concept of balancing chemical equation in chemistry. It is expected that students will improve their understanding in this concept and students interest in chemistry. This study examined how by using coloured blocks will help students understand the concept of balancing chemical equation which is an important concept to master in Form 4 Chemistry. Using pre and post-test control group design, the study involved a comparison between a control group (n=20) which were taught using the conventional chalk and talk method to balance chemical equation while the treatment group (n=20) were taught to balance chemical equations using coloured blocks. After pre-test, there was a significant difference between control and treatment group on their post-test scores with effect size of 1.31. Students who had used coloured blocks to balance chemical equations showed significant development in their post-test compared to the students who were taught using the conventional method. Students also showed high interest in chemistry upon using coloured blocks in teaching the concept of balancing chemical equation. The research results recommended the use of coloured blocks as a potential tool to teach the concept of balancing chemical equations..